Classical channel bandwidth requirements in continuous variable quantum key distribution systems - Margarida Almeida; Daniel Pereira; Armando N. Pinto; Nuno A. Silva (IET Quantum Communication)
Abstract The reconciliation method for continuous variable quantum key distribution systems is usually chosen based on its reconciliation efficiency. Nonetheless, one must also consider the requirements of each reconciliation method in terms of the amount of information transmitted on the classical channel. Such may limit the achievable key rates. For instance, multidimensional reconciliation of dimension 8 demands a classical channel bandwidth 43 times greater than that of the quantum channel baud rate. Decreasing the dimension to 4 halves the required bandwidth, allowing for higher quantum channel baud rates and higher key rates for shorter transmission distances, despite the lesser reconciliation performance.